INTERNALIZATION OF ISLAMIC VALUES IN AN URBAN MUSLIM SOCIETY: A CASE STUDY OF DIGITAL LEARNING AT MUHAMMADIYAH UNIVERSITIES IN YOGYAKARTA - David Sulistiawan Aditya; M. Nurdin Zuhdi (Akademika : Jurnal Pemikiran Islam, 2023)
As the majority religion, Islam in Indonesia is not directly proportional to Islamic values which should be displayed in the form of daily behaviour. Therefore, internalizing Islamic values, especially in the learning process in higher education, is of paramount important. Internalization of Islamic values is an aspect that is often overlooked in learning discussions, particularly in online learning. The issues raised in online learning discussions are more about methods and approaches in the learning process and very rarely to touch on the value aspect. In the context of Muhammadiyah higher education (PTM), instilling Islamic values as the core of its character education is a challenge for lecturers and students. In particular, those who live in urban areas which are full of challenges. This study explores challenges in internalizing Islamic values in digital learning at Muhammadiyah affiliated universities. Class observations and semi-structured interviews were conducted with 15 lecturers at three Muhammadiyah affiliated universities in Yogyakarta to garner an understanding of the internalization process and the challenges faced in this process. Data analysis was carried out using thematic analysis from Braun and Clarke. This study delineates that the process of internalizing Islamic values in the universities was still limited to the level of transformation and value transactions and has not yet touched on trans-internalization of values. This is because there are four main challenges faced, namely technical, pedagogical, psychological and semantic challenges. The implications and factors related to these four challenges are discussed in more depth in this paper.